Strongly reduced lattice thermal conductivity in Sn-doped rare-earth (M) filled skutterudites MxCo4Sb12−ySny, promoted by Sb–Sn disordering and phase segregation. Issue 42 (3rd August 2021) - Gainza, J.; Serrano-Sánchez, F.; Nemes, N. M.; Dura, O. J.; Martínez, J. L.; Fauth, F.; Alonso, J. A.
Abstract : Three effects act as phonon scatterers: rattling of M at 8 a cages, phase segregation, and intrinsic disorder introduced by Sn substitution, resulting in minimum k values. High filling fraction in Sn-doped phases pave the way to tune the carrier density in skutterudites. Abstract : CoSb3 thermoelectric skutterudite has been filled with rare-earth metals (M = La, Ce, Yb) and partially doped with Sn in specimens of M x Co4 Sb12− y Sn y stoichiometry. This has been achieved under high-pressure conditions at 3.5 GPa in a piston-cylinder hydrostatic press. A structural investigation using synchrotron X-ray diffraction data reveals a phase segregation in twin skutterudite phases with filling fraction fluctuation and different unit-cell sizes. As a result of three effects acting as phonon scatterers, namely the rattling effect of M at the wide 8 a cages of the cubic Im 3̄ structure, the phase segregation, and the intrinsic disorder introduced by Sn substitution at the Sb sublattice, the total thermal conductivity ( κ ) dramatically falls to reach minimum values under 2 W m −1 K −1, well below those typically exhibited by other thermoelectric materials based upon single-filled skutterudites. The power factor is substantially enhanced to 1.11 mW m −1 K −2 in Yb0.5 Co4 Sb11.6 Sn0.4 with respect to the unfilled composition, as a result of the charge transfer promoted by the filler.